2020
DOI: 10.3389/fmed.2020.576457
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Findings of COVID-19 Patients Admitted to Intensive Care Units in Guangdong Province, China: A Multicenter, Retrospective, Observational Study

Abstract: Background: Information about critically ill patients with coronavirus disease 2019 (COVID-19) in China but outside of Wuhan is scarce. We aimed to describe the clinical features, treatment, and outcomes of patients with COVID-19 admitted to the intensive care unit (ICU) in Guangdong Province. Methods: In this multicenter, retrospective, observational study, we enrolled consecutive patients with COVID-19 who were admitted to seven ICUs in Guangdong Province. Demographic data, symptoms, laboratory findings, com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Distinct from the characteristics of critically ill COVID-19 patients reported in Wuhan and other epicenters of the outbreak ( 4 7 ), patients in Guangdong were managed by a group of trained intensivists and specialist nurses with sufficient ventilators, extracorporeal membrane oxygenation (ECMO) equipment, and personal protective equipment. Moreover, as shown in our preprint data ( 12 ), the relatively low APACHE II and SOFA scores (the median APACHE II and SOFA scores was 14 and 4.0, respectively), of all patients at ICU admission indicated that fewer critically ill patients were admitted to the ICU to receive high intensity monitoring and prompt intensive care interventions. Besides, in our preprint study, 9 patients received ECMO due to a low but not too low PaO 2 /FiO 2 ratio [85.2 (58.3–103.4) mmHg] or a high but not too high PaCO 2 level [59.2 (53.5–68.9) mmHg], indicating early ECMO was initiated in patients presenting rapidly progressive respiratory failure (criteria for ECMO initiation: PaO 2 /FiO 2 from 120 to 100 mmHg and/or PaCO 2 from 50 to 55 mmHg, <4 h).…”
Section: Prompt Intensive Care Interventionssupporting
confidence: 52%
“…Distinct from the characteristics of critically ill COVID-19 patients reported in Wuhan and other epicenters of the outbreak ( 4 7 ), patients in Guangdong were managed by a group of trained intensivists and specialist nurses with sufficient ventilators, extracorporeal membrane oxygenation (ECMO) equipment, and personal protective equipment. Moreover, as shown in our preprint data ( 12 ), the relatively low APACHE II and SOFA scores (the median APACHE II and SOFA scores was 14 and 4.0, respectively), of all patients at ICU admission indicated that fewer critically ill patients were admitted to the ICU to receive high intensity monitoring and prompt intensive care interventions. Besides, in our preprint study, 9 patients received ECMO due to a low but not too low PaO 2 /FiO 2 ratio [85.2 (58.3–103.4) mmHg] or a high but not too high PaCO 2 level [59.2 (53.5–68.9) mmHg], indicating early ECMO was initiated in patients presenting rapidly progressive respiratory failure (criteria for ECMO initiation: PaO 2 /FiO 2 from 120 to 100 mmHg and/or PaCO 2 from 50 to 55 mmHg, <4 h).…”
Section: Prompt Intensive Care Interventionssupporting
confidence: 52%
“…Another study of 45 patients including 20 intubated patients had APACHE-II score of 14 and SOFA score of 4 showing a higher risk for intubation. Additionally, SOFA score correlated with lymphocytopenia and elevated LDH [27].…”
Section: Discussionmentioning
confidence: 90%
“…Around 9.35% of patients included in this study were asymptomatic during the initial assessment. Fever and respiratory symptoms were most common among the patients, reported in numerous other studies [21,27,28]. While several studies from China [28,29], Uzbekistan [30], and Brazil [31] reported weakness or fatigue as a common symptom, only 8% (n = 31 out of 377) of the patients reported that they experienced weakness during initial triage at the hospital.…”
Section: Discussionmentioning
confidence: 82%
“…The lower SpO2 level or severe illness was signi cantly associated with older age and the presence of any comorbidity. Besides, the severe illness was signi cantly associated with radiological ndings of Pneumonia [34], higher creatinine [27,35], c-reactive protein [20,35], and Neutrophil Lymphocyte ratio [36][37][38]. A higher proportion of patients with low SpO2 levels frequently received antibiotics, anticoagulants, and glucocorticoid therapy.…”
Section: Discussionmentioning
confidence: 99%